# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime }+3 y^{\prime }+2 y = 4 \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }-8 y = 3 \,{\mathrm e}^{-2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+4 y = 2 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = \sinh \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = \cos \left (3 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = \sin \left (3 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = 2 \sec \left (3 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \csc \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = \sin \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = x \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }-y = 72 x^{5}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = x^{3}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = x^{4}
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+3 y = 8 x^{{4}/{3}}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+y = \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = x^{2}-1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 2 \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+9 x = 10 \cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x = 5 \sin \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+100 x = 225 \cos \left (5 t \right )+300 \sin \left (5 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+25 x = 90 \cos \left (4 t \right )
\] |
✓ |
✓ |
|
\[
{}m x^{\prime \prime }+k x = F_{0} \cos \left (\omega t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+4 x = 10 \cos \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+3 x^{\prime }+5 x = -4 \cos \left (5 t \right )
\] |
✓ |
✓ |
|
\[
{}2 x^{\prime \prime }+2 x^{\prime }+x = 3 \sin \left (10 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+3 x^{\prime }+3 x = 8 \cos \left (10 t \right )+6 \sin \left (10 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+5 x = 10 \cos \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+6 x^{\prime }+13 x = 10 \sin \left (5 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+2 x^{\prime }+26 x = 600 \cos \left (10 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+8 x^{\prime }+25 x = 200 \cos \left (t \right )+520 \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+2 x^{\prime }+2 x = 2 \cos \left (\omega t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+5 x = 10 \cos \left (\omega t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+6 x^{\prime }+45 x = 50 \cos \left (\omega t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+10 x^{\prime }+650 x = 100 \cos \left (\omega t \right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x y^{\prime }+\left (x^{2}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+3 y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }-y^{\prime }+36 x^{3} y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-5 x y^{\prime }+\left (x +8\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}36 x^{2} y^{\prime \prime }+60 x y^{\prime }+\left (9 x^{3}-5\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}16 x^{2} y^{\prime \prime }+24 x y^{\prime }+\left (144 x^{3}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+3 x y^{\prime }+\left (x^{2}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }-12 x y^{\prime }+\left (15+16 x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}16 x^{2} y^{\prime \prime }-\left (-144 x^{3}+5\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-3 x y^{\prime }-2 \left (-x^{5}+14\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x^{4} y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+4 x^{3} y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+2 y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+9 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-x^{\prime }-2 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+8 x^{\prime }+15 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = \sin \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x = \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = \cos \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+9 x = 1
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+3 x = 1
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+3 x^{\prime }+2 x = t
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+6 x^{\prime }+25 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-6 x^{\prime }+8 x = 2
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-4 x = 3 t
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+8 x = {\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+13 x = t \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+6 x^{\prime }+18 x = \cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+9 x = 6 \cos \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+\frac {2 x^{\prime }}{5}+\frac {226 x}{25} = 6 \,{\mathrm e}^{-\frac {t}{5}} \cos \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}t x^{\prime \prime }+\left (t -2\right ) x^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}t x^{\prime \prime }+\left (3 t -1\right ) x^{\prime }+3 x = 0
\] |
✓ |
✓ |
|
\[
{}t x^{\prime \prime }-\left (4 t +1\right ) x^{\prime }+2 \left (2 t +1\right ) x = 0
\] |
✓ |
✓ |
|
\[
{}t x^{\prime \prime }+2 \left (t -1\right ) x^{\prime }-2 x = 0
\] |
✓ |
✓ |
|
\[
{}t x^{\prime \prime }-2 x^{\prime }+t x = 0
\] |
✓ |
✓ |
|
\[
{}t x^{\prime \prime }+\left (4 t -2\right ) x^{\prime }+\left (13 t -4\right ) x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x = f \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+2 x^{\prime }+x = f \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+13 x = f \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x = \delta \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x = \delta \left (t \right )+\delta \left (t -\pi \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+4 x = 1+\delta \left (t -2\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+2 x^{\prime }+x = t +\delta \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+2 x^{\prime }+2 x = 2 \delta \left (t -\pi \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+9 x = \delta \left (t -3 \pi \right )+\cos \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+5 x = \delta \left (t -\pi \right )+\delta \left (t -2 \pi \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+2 x^{\prime }+x = \delta \left (t \right )-\delta \left (t -2\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x = f \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+6 x^{\prime }+9 x = f \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+6 x^{\prime }+8 x = f \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+8 x = f \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-10 y^{\prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+13 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+2 x y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|